Effect of 6E Learning by Design on Students’ Problem Solving Skills in Sound Waves - Isnawati; Darmadi, I Wayan; Nurjannah; Miftah (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to examine the effect of the 6E Learning by Design model on students’ problem-solving skills in learning sound wave material at MAN 2 Palu City. The research used a quasi-experimental method with a nonequivalent pretest-posttest control group design. The population consisted of all class XI MIPA students. The sample was selected using purposive sampling, with class XI MIPA I (n = 34) as the control class and class XI MIPA J (n = 34) as the experimental class. The instrument used was a problem-solving skills open-ended test. The results showed that the increase in problem-solving skills scores in the experimental class was higher than in the control class, with an N-gain value of 0,685, categorized as moderate. Hypothesis testing was conducted using the Mann-Whitney U test at a significance level of 0,05. Furthermore, the effect size was 1,4 (d ≥ 1.3), indicating a strong effect. These results indicate that the 6E Learning by Design model effectively improves students’ problem-solving skills on sound wave material.